2019
DOI: 10.1063/1.5088143
|View full text |Cite
|
Sign up to set email alerts
|

Taylor-Couette flow of shear-thinning fluids

Abstract: The flow between two concentric cylinder, one of which is rotating (Taylor-Couette flow), has been the focus of extensive research, due to the number of flow instabilities that may occur and its use in various industrial applications. We examine Taylor-Couette flow of Newtonian and shear-thinning fluids (solutions of xanthan gum in water/glycerol) using a combination of Particle-Image Velocimetry and flow-visualisation for a wide range of Reynolds number, spanning the Circular Couette Flow, Taylor Vortex Flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 41 publications
(51 reference statements)
9
44
2
Order By: Relevance
“…The tendency for shear-thinning to cause a reduction in the critical Reynolds number has been noted in previous studies (Lockett et al 1992;Escudier et al 1995;Alibenyahia et al 2012;Cagney & Balabani 2019b). The elasticity also appears to be associated with a progressive destabilisation of the flow (figure 6c), which is not always the case for Boger fluids (Muller 2008), although it is not straightforward to disentangle the effects of shear-thinning and viscoelasticity.…”
Section: Overviewmentioning
confidence: 73%
See 1 more Smart Citation
“…The tendency for shear-thinning to cause a reduction in the critical Reynolds number has been noted in previous studies (Lockett et al 1992;Escudier et al 1995;Alibenyahia et al 2012;Cagney & Balabani 2019b). The elasticity also appears to be associated with a progressive destabilisation of the flow (figure 6c), which is not always the case for Boger fluids (Muller 2008), although it is not straightforward to disentangle the effects of shear-thinning and viscoelasticity.…”
Section: Overviewmentioning
confidence: 73%
“…The no slip condition at the ends means that the first jet near the ends (i.e. one vortex spacing away from the end walls) move fluid radially outward (Imomoh et al 2010;Cagney & Balabani 2019b); using this information, it can be seen from figure 12(a) that the wavy instability is strongest at the inward jets and relatively weak at the outward jets, regardless of the axial location.…”
Section: Overviewmentioning
confidence: 99%
“…Actually, there is an interplay between nonlinear inertia terms and nonlinear viscous terms. Based on the experimental results such the streamline patterns in Taylor vortices represented by Escudier et al [22] and the spatiotemporal plots reported by Cagney and Balabani [24] for different shear-thinning fluids, the Taylor vortex flow observed can be considered as periodic with a wavenumber k close to the critical value k c . Here we take k = k c and we concentrate on solutions that consist of this mode plus modes that can be generated from it through the nonlinearity.…”
Section: I2 Objectives Methodology and Outline Of The Papermentioning
confidence: 99%
“…This last uncertainty is maximal when the slope of the curve in Fig. 2 is the steepest, i.e., at the lowest effective flow index (as defined in Cagney and Balabani (2019)). This is here the case for shear rates around 4 s −1 .…”
Section: Viscosity Estimation and Statisticsmentioning
confidence: 99%